Creating shared learning spaces through collaborative enquiry tasks - Max, C (2008)
Conceived initially as a collaborative task in the new Initial Teacher Education (ITE) programme of the University of Luxembourg, the "Collaborative Classroom Inquiry" (CCI) mediates collaboration and interaction between the academic and the professional context. The programme strives to interrelate academic concerns with field activities in a meaning making sense through specific learning spaces where all the stakeholders, i.e. students, academic tutor and internship teacher, meet and create shared practices with regard to the common object "educating student teachers across boundaries". As a recently developed educational tool, the CCI crosses institutional boundaries and generates contradictions among the collaborating partners, which may be seen as a promising starting point for creating mutually relevant practices within and beyond this joint learning space, but also bearing considerable potential for breakdowns of further collaborations. The present contribution scrutinises the innovative potential of the CCI for generating change and development among the interacting partners through questions such as: Who is learning? What is learned? Why and how does learning occur?